THE EFFECT OF OPERATING CONDITIONS ON CRITICAL FLUX AND REVERSIBLE FOULING IN MEMBRANE FILTRATION USING GAS SPARGING TECHNIQUE - Harunsyah, Harunsyah; Sulaiman, Nik Meriam (Politeknik Negeri Lhokseumawe, 2003)
Gas sparging method utilizing injection of nitrogen gas was employed during the ultrafiltration of the natural rubber effluent (latex serum). The objective of this research was to investigate the effect of gas sparging on the critical flux and the observed reversible cake layer resistance during the ultrafiltration of skim latex serum. Experiments were conducted using a 100 kDa MWCO tubular membrane (PCI Membrane System) mounted vertically. The effect of operating parameters, such as feed flow rate, concentration and transmembrane pressure were investigated. The results showed that when the feed flow rate was increased, the permeate was correspondingly increased and the reversible cake resistance decreased. In this research a feed flow rate of 1400 ml/min and transmembrane pressure of 13.00 psig resulted in the maximum total permeate flux of 70.80 L/m2h. Results from this study obtained so far showed that the use of gas sparging has been able to increase total permeate flux between 8.3% and 145.3% compared to non-gas sparged condition. Critical flux occurrence was increased to 82.63% above the value obtained for non-sparged condition and applied transmembrane pressure can be reduced to 2.4% of the non-gas sparged condition.Keyword: skim latex serum, reversible fouling, gas sparged, critical flux